Stability and in vivo efficiency of natural cosmetic emulsion systems with the addition of vegetable oils - Jana Pavlačková; Klára Kovacsová; Petr Radiměřský; Pavlína Egner; Jana Sedlaříková; Pavel Mokrejš (Universidade de São Paulo, 2018)
The aim of the paper is to test stability and biophysical properties of hydrophilic and lipophilic emulsions with selected vegetable seed oils: Limnanthes alba, Prunus amygdalus dulcis, Cannabis sativa, Rosa rubiginosa and Hellianthus annuus. Biophysical properties of emulsions are investigated in vivo using non-invasive instrumental methods (corneometry, tewametry and pH) in a group of 12 healthy women volunteers. Their stability profiles (colour, phase separation and centrifugation) under various temperatures (9, 25, 37 and 57 °C) and storage time (24 hours, 2, 7, 14, 21 and 28 days) were monitored. The moisturising activities of the emulsions supplemented with various oils were comparable. The lipophilic emulsions showed a better ability to improve the condition of the skin barrier due to formation of a surface lipid film. The tested formulations regulated the pH of the skin towards neutral values. Lipophilic emulsions showed earlier phase separation and changes in colour. The greatest resistance to thermal stress during storage was observed for the emulsion bases. Emulsions containing oils, except for those with rosehip and hempseed oils, were stable up to the temperature of 37 °C. The studied emulsion systems are excellent vehicles of vegetable oils and exhibit relatively good stability, benefiting the natural properties of skin.